2019
DOI: 10.1371/journal.pone.0216954
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, features, and prognosis of immune-related adverse events involving the thyroid gland induced by nivolumab

Abstract: Background Blocking the PD-1 pathway induces immune-related adverse events (irAEs) which often involve the thyroid gland (thyroid irAEs). Clinical features of a thyroid irAE including its predictability and relationship to prognosis remain to be elucidated. Methods Two hundred consecutive patients treated with nivolumab at Kyoto University Hospital between September 1, 2014 and August 31, 2017 were included in a retrospective cohort study. We systematically determined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 21 publications
(37 reference statements)
10
93
1
9
Order By: Relevance
“…Further, patients with any irAE showed longer OSs than those without irAEs [17]. Of note, we found no specific irAE type being associated with longer survival, contrary to some reported results [26,27]. Thus, more clinical evidence is required to elucidate the association mechanisms between irAEs and ICIs efficacy.…”
Section: Discussioncontrasting
confidence: 82%
“…Further, patients with any irAE showed longer OSs than those without irAEs [17]. Of note, we found no specific irAE type being associated with longer survival, contrary to some reported results [26,27]. Thus, more clinical evidence is required to elucidate the association mechanisms between irAEs and ICIs efficacy.…”
Section: Discussioncontrasting
confidence: 82%
“…In the case, eosinophilia, thrombocytopenia, ESR/CRP/LDH elevation, and liver dysfunction might be important for early detection of thyrotoxicosis. Yamauchi, et al reported that patients with thyroid uptake of FDG-PET before nivolumab therapy showed high incidences of overt thyroid irAE [34]. Routine check-up of those predictive factors for thyroid irAE as well as serum FT3, FT4 and TSH levels are recommended.…”
Section: Clinical Manifestation Of Thyroid Iraementioning
confidence: 99%
“…If anti-tumor therapy is effective, continuation of ICI treatment is warranted with proper management of thyroid irAE [32]. In addition, development of thyroid irAE was reported to have positive correlation with feasible outcome of lung cancer [34]. In the future, identification of individuals who are susceptible to thyroid irAEs is necessary (age, gender, genetic predispositions such as HLA and immune-checkpoint molecules).…”
Section: Conclusion Of Thyroid Iraementioning
confidence: 99%
“…A number of recent studies has supported this hypothesis by showing favorable outcomes for patients with non-small cell lung cancer (NSCLC) and melanoma who developed various irAEs in response to immune checkpoint inhibition [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, a definite conclusion has not been drawn based on the findings from each single study, as contradictory results exist [23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%